Czech Republic : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper on the Czech Republic presents an analysis of various aspects of population aging: its macroeconomic effects; impact on fiscal sustainability; and implications for private savings. The paper simulates the macroeconomic effects of population aging in the Czech Republic using an overlapping-generations model. It finds that aging can significantly weaken the outlook for economic growth and living standards. The paper evaluates the fiscal implications of aging using a generational-accounting framework. It also evaluates the monetary policy implications of capital account volatility-as the relative importance of portfolio flows increases.